2008
DOI: 10.1038/leu.2008.346
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of constitutive and BCR-induced Syk activation downregulates Mcl-1 and induces apoptosis in chronic lymphocytic leukemia B cells

Abstract: The protein kinase Syk is a key mediator of proximal B-cell receptor (BCR) signaling. Following antigen stimulation, Syk is recruited to the BCR and becomes activated by phosphorylation at Y352. Recently, Syk was found to be constitutively phosphorylated in several common B-cell lymphoma subtypes, indicating a role for antigen-independent Syk activation in the pathogenesis of these diseases. We now report that Syk is constitutively phosphorylated on the activating Y352 residue in chronic lymphocytic leukemia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
186
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(207 citation statements)
references
References 62 publications
17
186
2
2
Order By: Relevance
“…With our Fab‐PLA technique, we found that these receptors not only have an open conformation, but are also in close proximity to the CD19 protein, thus combining PI3K signaling with active ITAM signaling (unpublished observation). In line with this, the growth of B‐CLL cells is blocked by Syk or PI3K inhibitors (Gobessi et al , 2009; Danilov, 2013). The BCR is also stably expressed on all ABC‐DLBCLs, although the growth of these tumors is driven more by active NFkB than by PI3K signaling (Davis et al , 2010).…”
Section: Discussionmentioning
confidence: 84%
“…With our Fab‐PLA technique, we found that these receptors not only have an open conformation, but are also in close proximity to the CD19 protein, thus combining PI3K signaling with active ITAM signaling (unpublished observation). In line with this, the growth of B‐CLL cells is blocked by Syk or PI3K inhibitors (Gobessi et al , 2009; Danilov, 2013). The BCR is also stably expressed on all ABC‐DLBCLs, although the growth of these tumors is driven more by active NFkB than by PI3K signaling (Davis et al , 2010).…”
Section: Discussionmentioning
confidence: 84%
“…SYK has recently emerged as a potential new molecular target for the treatment of B-lineage leukemias and lymphomas (29)(30)(31)(32)(33)(34). Compelling evidence from gene profiling studies indicates that abundant STAT3 expression in ALL is associated with chemotherapy and steroid resistance (35)(36)(37).…”
Section: Syk Plays a Pivotal Role In Os-induced Activation Of Stat3 Imentioning
confidence: 99%
“…However, in the context of STAT3 activation after OS, the kinase activity of SYK is clearly required for tyrosine phosphorylation of STAT3, as PV did not activate STAT3 in SYK − DT40 cells reconstituted with a kinase domain-mutant SYK and inhibition of the kinase activity of SYK with small molecule inhibitors SYKINH-61 or PCT prevented OS-induced STAT3 activation in the absence of any alteration in SYK protein levels. Likewise, the kinase activity of SYK has been shown to be essential for its reported antiapoptotic activity in the context of OS (9), tonic or ligand-mediated BCR signaling (31,33,34), and cytokine signaling (55).…”
Section: Syk Plays a Pivotal Role In Os-induced Activation Of Stat3 Imentioning
confidence: 99%
“…The binding of Syk to the receptor activates the enzyme, which becomes phosphorylated on tyrosine and functions as both a kinase and a scaffold to couple the receptor to downstream effectors of multiple signaling pathways. In certain malignancies of B-cell origin, it is tonic signaling from the BCR that is proposed to activate Syk to promote cell survival (4,7,8). Interestingly, the repertoire of cells in which Syk functions as a prosurvival factor extends to tumors of B-cell origin that have not yet rearranged immunoglobulin genes, hematological malignancies not of B-cell origin, and nonhematological cancers, such as retinoblastoma and certain carcinomas of the lung and pancreas (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Constitutively active Syk has been reported to promote the survival of non-Hodgkin's lymphoma, acute lymphoblastic leukemia, chronic lymphocytic leukemia, and Epstein-Barr virus-associated B-cell lymphoma (3)(4)(5)(6)(7)(8)(9)(10)(11). The inhibition of Syk also promotes the differentiation of acute myeloid leukemia (AML) and attenuates the growth of AML cell lines and primary blasts (12,13).…”
mentioning
confidence: 99%